Did the Great Recession change the regional reputation premium for wine in the US? - Omer Gokcekus; Clare M. Finnegan (Wine Economics and Policy, 2013)
Wine is an experience good and also (at least under certain circumstances and to a certain extent) a conspicuous consumption good. As such, wine buyers should be willing to pay a premium for regional reputation to avoid risk and to send signals about their wealth and social status. At the same time, wine is an annually produced good; every year new bottles arrive to wine stores. Accordingly, a wine store's manager has to periodically clear the store's inventory. Statistical analyses indicate that, during the Great Recession in the US, two developments-a substantial decline in income and a rise in information sharing via the internet and social media-had a dampening effect on the regional reputation premium and lowered the price-quality ratio differences among different wine regions. Moreover, during the same time period, the discount rates necessary to clear inventories significantly increased.
Keywords: 330; Consumer behavior; Price-quality ratio; Regional reputation premium